The use of biochemical markers of bone turnover in osteoporosis - Allende-Vigo, Myriam Z. (Puerto Rico Health Sciences Journal, 2007)
Objective: Present evidence-based recommendations on the use of biochemical markers of bone turnover in the management of osteoporosis. Methods: The English literature from 1999 to 2005 was reviewed by using data sources from MEDLINE. Results: Measurement of biochemical markers of bone turnover helps us identify a high bone turnover rate. Elevated levels of these markers points towards a pathology and at an accelerated loss of bone mass. Its main utility is in documenting the response to therapy. They have a limited role in the follow-up of patients with osteoporosis. To be useful, bone markers must be measured at baseline and periodically after the beginning of therapy. A fall of on fifty (50%) percent in the levels of resorption markers between the third and sixth month of therapy predicts a good response. Bone markers can not be used to establish the diagnosis of osteoporosis. Neither do they measure bone mass. Markers are not capable of predicting future loss of bone mass in an individual nor do they correlate with the occurrence of previous fractures. The greatest limitation of these measurements is not being able to measure bone remodeling in the individual subject. Bone resorption markers are more frequently used than those of formation. The levels of the markers can identify the failures to the therapy and responses to therapy. Lack of reduction in the resorption markers could indicate lack of compliance with therapy, problems of absorption of the medication or lack in response to treatment. There may be problems with the measurement and the interpretation of results of bone remodeling markers. Variability between individuals and intra-individual variability exist as well as inter-assay and intra-assay variability. Conclusion: Biochemical markers of bone turnover along with measurements of bone density can help optimize the management of osteoporosis. The use of the bone markers is not recommended in a routine form, but they can be of utility in situations of poor compliance with the therapy or when there are difficulties in the management of the treatment of osteoporosis.